Mô hình dự báo cho nền kinh tế nhỏ và mở của Việt Nam Phương pháp tiếp cận: BVAR-DSGE - Nguyễn Đức Trung; Nguyễn Hoàng Chung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This paper estimates a small-open DSGE model of the Vietnam economy, constructed and adjusted for forecasting the macroeconomic variables such as output growth, inflation, policy interest rates, exchange rate, and terms of trade. In contrast to models with purely statistical platforms, which are often used for forecasting, the paper applies the DSGE model to a small and open economy like Vietnam to provide prior information for the BVAR model. The results of the study show the relative suitability of the method and the compatibility between the theoretical models and the actual data for establishing a meaningful forecasting model for Vietnam.